Saturday Morning Science programs: a model to increase diversity in the biosciences. - Phillips JL; Harris TB; Ihedigbo KM; Hawkins J; Phillips, James L; Harris, Toi Blakley; Ihedigbo, Kara M Green; Hawkins, Jacqueline (Journal of the National Medical Association)
Purpose: To examine a pathway program for middle and high school students from underrepresented backgrounds designed to foster career interest in the biomedical sciences. In 2002, the Institute of Medicine released a report entitled Unequal Treatment, which examined the racial and ethnic disparities in health and health care within the United States and encouraged the development of a diverse health care workforce as a means to reduce health care disparities.Procedures: Saturday Morning Science (SMS) is a program model presented as a pipeline strategy that addresses this specific recommendation. SMS is a 10-week program that emphasized the importance of science and math. Post-SMS evaluations were conducted to assess biomedical career knowledge, attitudes regarding future career plans, and the effectiveness of the program.Findings: A total of 87.5% of middle and high school students who were enrolled in SMS completed the program (113 of 130). Seventy percent of SMS participants were underrepresented minorities. Snapshot program evaluation data exposed new ideas about science (strongly agree/agree, 98%; 64 of 65), exposed new ideas about medicine (strongly agree/agree, 97%; 63 of 65, and increased desire to enter science related field (strongly agree/agree 82% (53 of 65).Conclusions: SMS was designed to motivate students of underrepresented ethnic backgrounds from middle through high school to attend college and prepare for careers in the health sciences. SMS students had the opportunity to interact with scientists, physicians, medical and graduate students, and other academicians. They provided direction and guidance to ensure that students had meaningful experiences specifically designed to expose them to opportunities in the biosciences.